Perceptions and experience of veterinary surgery residents with minimally invasive surgery simulation training. (6th August 2019) - Balsa, Ingrid M.; Giuffrida, Michelle A.; Culp, William T. N.; Mayhew, Philipp D.
Abstract: Objective: To determine access to and use of minimally invasive surgery (MIS) simulators among American College of Veterinary Surgeons (ACVS) small animal residents and to identify barriers to simulator use and perceptions of simulator training. Study design: Voluntary online survey. Sample population: One hundred forty‐one ACVS small animal residents. Methods: American College of Veterinary Surgeons residents were identified by contacting ACVS residency program directors. An emailed online survey was sent to residents along with a reminder email 2 weeks later. All surveys were collected within 1 month. Participation was voluntary but incentivized. Results: Response rate to the survey was 79 of 141 (56%) residents. Twenty‐eight of 77 (36%) residents have access to a simulator, with box simulators being most common. Lack of time was the most frequent reason for not using the simulator more. Sixty‐eight of 77 (88%) and 65 of 77 (65%) residents agreed or strongly agreed that simulator‐based training improves laparoscopic skills and that simulator skills are transferable to the operating room, respectively. Residents with access to a simulator were more comfortable with basic laparoscopic surgeries at the end of their residency than those without such access ( P = .04). Conclusion: There is substantial room for improved access to and use of MIS simulator training in ACVS residency programs. Despite lack of simulator access, residents believed that simulator training improved their skill and comfort level with basic laparoscopic procedures. Clinical significance: The results of this study inform us about access to and perceptions of MIS simulator training among residents. This information is important to surgeons responsible for training residents and may help guide the creation of a surgical skills curriculum.